Representation of the Meaning of Indung in Artworks - Maulina, Rini; Sabana, Setiawan; Damayanti, Nuning Yanti; Muhtadin, Teddi (Harmonia: Journal of Arts Research and Education, 2021)
Indung means mother in Sundanese. Indung in Sundanese culture is found in Paribasa, Babasan, Carita Pantun, Waditra (Sundanese traditional musical instrument), traditional ceremonies, and others. The word indung, which is found in almost all elements of Sundanese culture and manifests in Sundanese artifacts, has an invisible meaning. The meaning of indung in the perspective of Sundanese culture that exists in today’s society has not been explored. The meaning of indung from a cultural perspective needs to be searched for. There have not been found artworks with the theme of indung from a Sundanese cultural perspective, so it is necessary to explore representations in artworks. This study employs the Art-based Research method, in which an investigation is carried out on the data, and the results are represented in artworks. Through questionnaires, interviews, and literature studies, the meaning of indung is extracted and then tabulated to be classified and analyzed. The results of data processing showed that indung has many meanings, the result of converging data from the literature, questionnaire and interview the whole there are 17 meanings, among which the nurse, angel, house, huge, source of life, earth, embrace, harmony, the center of life, and love. The results of data processing are represented in artworks. Artworks made based on the meaning of indung are limited to three titles, namely Sumber Kehidupan (Source of Life), Merangkul (Embracing), and Rumah yang Hangat (Warm Home). The visual exploration contained in the three titles is made using stylized forms with a decorative style, using elements of motifs and colors from West Javanese batik. The media and techniques used are found in written batik. The results of the visualization of the meaning of indung of the three artworks that are created can be concluded that the meaning of indung cannot be symbolized singly.